Somatosensory Evoked Potential and Transcranial Doppler Monitoring to Guide Shunting in Carotid Endarterectomy - Seidel, Kathleen; Jeschko, Johannes; Schucht, Philippe; Bervini, David; Fung, Christian; Krejci, Vladimir; Z'Graggen, Werner; Fischer, Urs; Arnold, Marcel; Goldberg, Johannes; Raabe, Andreas; Beck, Juergen (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objective Clamping of the internal carotid artery (ICA) during carotid endarterectomy (CEA) is a critical step. In our neurosurgical department, CEAs are performed with transcranial Doppler (TCD) and somatosensory evoked potential (SEP) monitoring with a 50% flow velocity/amplitude decrement warning criteria for shunting. The aim of our study was to evaluate our protocol with immediate neurologic deficits after surgery for the primary end point.Methods This is a single-center retrospective cohort study of symptomatic and asymptomatic ICA stenosis patients from January 2012 to June 2015. Only those cases in which CEA was performed with both modalities (TCD and SEP) were included. The Mann-Whitney U test was applied to evaluate TCD and SEP ratios based on immediate postoperative neurologic deficits.Results A total of 144 patients were included, 120 (83.3%) with symptomatic ICA stenosis. The primary end point was met by six patients (4.2%); all of them were patients with a symptomatic ICA stenosis. The stroke and death rate was 1.4%. Ratios of SEP amplitudes demonstrated significant differences between patients with and without an immediate postoperative neurologic deficit at the time of ICA clamping (p = 0.005), ICA clamping at 10 minutes (p = 0.044), and ICA reperfusion (p = 0.005). Ratios of TCD flow velocity showed no significant difference at all critical steps.Conclusion In this retrospective series of simultaneous TCD and SEP monitoring during CEA surgery of predominantly symptomatic ICA stenosis patients, the stroke and death rate was 1.4%. SEP seemed to be superior to TCD in predicting the need for an intraoperative shunt and for predicting temporary postoperative deficits. Further prospective studies are needed.
Keywords: carotid endarterectomy; intraoperative neurophysiologic monitoring; somatosensory evoked potential; shunt; transcranial Doppler sonography; warning criteria